Do we need anti-obesity drugs? - Hainer, Vojtěch; Hainerová, Irena Aldhoon (Diabetes/metabolism research and reviews, 2012)
The increasing global prevalence of obesity urgently requires an implementation of efficient preventive and therapeutic measures. Weight loss and its maintenance should be considered one of the most important strategies to reduce the incidence of obesity-related co-morbidities such as diabetes and cardiovascular diseases. Lifestyle modification focused on diet and physical activity represents the essential component of any kind of weight management. However, only an intensive lifestyle intervention can be efficient in terms of long-term weight loss. Anti-obesity drugs affect different targets in the central nervous system or peripheral tissues and improve regulatory and metabolic disturbances that contribute to the development of obesity. Anti-obesity medications provide modest additional fat loss to that achieved by lifestyle modification alone, reduce visceral fat stores, improve programme adherence, weight loss maintenance, diminish obesity-related health risks and improve a quality of life. Anti-obesity drugs do play a role in weight management. Their replacement with placebo is followed by weight regain. Due to adverse events, several anti-obesity drugs were withdrawn from the market over the past few years and currently only orlistat remains available for long-term obesity management. Drug withdrawals, failure of clinical trials with several new anti-obesity compounds as well as inappropriate demands of drug regulating agencies concerning the study protocol led to scepticism about the perspectives in the pharmacotherapy of obesity. However, recently developed anti-obesity medications such as gut hormone analogues and drug combinations provided encouraging results in terms of weight loss, safety and improvement of cardio-metabolic health risks.
Keywords: Life Style; životní styl; Anti-Obesity Agents; Obesity; Weight Loss; lidé; obezita; hmotnostní úbytek; látky proti obezitě; Humans